Small hydroelectric engineering practice - Brown J Guthrie (Delhi CBS Publishers & Distributers, 1984)
"Small Hydroelectric Engineering Practice is a comprehensive reference book covering all aspects of identifying, building, and operating hydroelectric schemes between 500 kW and 50 MW. In this range of outputs there are many options for all aspects of the scheme and the book aims to provide all the information needed to ensure that the best options are chosen.Small hydroelectric schemes are usually built against a limited budget so it is extremely important that the concept design is optimum and every component is designed to maximise the benefit and mini- mise the cost. As operating costs are often a high proportion of the income it is very important to make sure that everything is designed to be simple, reliable and long lasting. The book is based on the experience gained over 45 years on the overall and detailed design, construction, commissioning and refurbishment of many small hydropower schemes in New Zealand and overseas. It includes contributions from experts in the field of intakes, water diversion structures, geology, canals, painting, economics and environmen- tal aspects of hydropower development. It is intensely practical with many drawings and photographs of schemes designed and commissioned by Leyland Consultants and others. There are also sections on preparing specifications, tender assessment, operation and maintenance and lessons from failures. The book includes a CD with some relevant papers, spreadsheet programs for analysing aspects of small hydropower development and many arrangement drawings and detail designs for gates, penstocks, electrical systems and control systems. Typical specifications for generating plant are also included. The spreadsheets will be useful during the feasibility stage and the drawings provide valuable information on critical aspects of detailed design. Consultants, developers, designers, builders and operators of small hydroelectric schemes will find this book invaluable."--
0
Keywords: Small scale hydropower; MCE; TECHNOLOGY & ENGINEERING / Civil / Dams & Reservoirs; TECHNOLOGY & ENGINEERING / Environmental / General; TECHNOLOGY & ENGINEERING / Power Resources / Electrical